Extreme late-phase observation using coronary angioscopy until 7 years after sirolimus-eluting stent implantation. Issue 1 (January 2016) - Shimura, Tetsuro; Yamamoto, Masanori; Takano, Masamichi; Okamatsu, Kentaro; Inami, Shigenobu; Murakami, Daisuke; Munakata, Ryo; Inami, Toru; Kurihara, Osamu; Kano, Seiji; Seino, Yoshihiko; Shimizu, Wataru; et al.
Abstract : Background: Little is known about the very late-phase morphological vessel characteristics within the sirolimus-eluting stent (SES). Methods and results: We assessed a total of 12 patients with 15 SES implantations who underwent repeat angiographic and angioscopic procedures after 5 and 7 years. The degree of neointimal stent coverage (NSC) was classified as follows: grade 0, uncovered struts; grade 1, visible struts through a thin neointima; or grade 2, invisible struts with complete neointimal coverage. The maximum and minimum NSC grades were evaluated and the existence of in-stent thrombus was also recorded for all patients. The prevalence of a maximum NSC grade of 2 increased and that of a minimum NSC grade of 0 decreased, although there was no significant difference in prevalence between 5 and 7 years. One of four in-stent thrombus identified at 5 years had disappeared from 5 to 7 years and a new thrombus was found in another patient at 7 years. Thus, the incidence of in-stent thrombus did not change from 5 to 7 years. In one case, a thrombus was observed inside the angiographic aneurysmal change, but none of the thrombi were related to adverse events. Conclusion: This angioscopic study reported gradual arterial repair and continuous delayed healing associated with subclinical thrombus formation 7 years after SES deployment.